2020
DOI: 10.3390/genes12010021
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Reference Genes for Normalization of Gene Expression in Thermobia domestica (Insecta: Zygentoma: Lepismatidae)

Abstract: Zygentoma occupies a key evolutionary position for understanding the evolution of insect metamorphosis but has received little attention in terms of genetic analysis. To develop functional genomic studies in this insect, we evaluated five candidate internal reference genes for quantitative RT-PCR (qPCR) studies from Thermobia domestica, a representative species of Zygentoma, including Actin 5C (Actin5C), Elongation factor-1 alpha (EF1A), Ribosome protein S26 (RPS26), Ribosome protein L32 (RPL32), and Superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…More convincing results were obtained when two genes were used for expression normalization ( Figures 5A,B ). Our results corroborate the current notion of using two or three genes for target gene expression normalization to enhance accuracy (Arya et al, 2017 ; Li et al, 2018c ; Wei et al, 2020 ; Bai et al, 2021 ; Fu and Meyer-Rochow, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…More convincing results were obtained when two genes were used for expression normalization ( Figures 5A,B ). Our results corroborate the current notion of using two or three genes for target gene expression normalization to enhance accuracy (Arya et al, 2017 ; Li et al, 2018c ; Wei et al, 2020 ; Bai et al, 2021 ; Fu and Meyer-Rochow, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…RPS3 also exhibited high stability under larval tissues in Lucilia sericata (Baumann et al, 2015 ). Similarly, RPL9 and RPL10 genes showed higher expression stability in different developmental stages and tissues of Sogatella furcifera (An et al, 2016 ), whereas RPS26 and RPL32 genes showed the same in Thermobia domestica (Bai et al, 2021 ). Furthermore, RPS18 and RPL13 genes showed the highest expression stability in Rhopalosiphum padi tissues (Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Some of the internal reference genes screened by us can be directly used in RNAi experiments after verification. For the tissues, the reference genes used by Thermobia domestica were RPS26 and RPL32 in the different tissues under dsRNA microinjection treatment [ 56 ]. RNAi studies of specific target genes usually also screen the suitable reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is also the most reliable method for detecting and quantifying transcriptional abundance [4]. When using RT-qPCR to study the expression levels of target genes, appropriate reference genes must be used to calibrate and standardize the experimental samples [5][6][7]. The reference genes should not be affected by external environments and should be stably expressed in various tissues or cells and under various experimental conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several genes have been confirmed as stable reference genes and are widely used when studying insects, such as glyceraldehyde 3-phosphate dehydrogenase (GAPDH), actin (ACT), translation elongation factor 1α (TEF-1α), phospholipase A2 (PLA2), arginine kinase (AK), tubulin (TUB), TATA binding protein (TBP), and ribosomal proteins [7,[16][17][18][19][20]. However, few reference genes are consistently expressed across all conditions (e.g., tissues, developmental stages, and experimental conditions) [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%